Multivariate integration of physicochemical and targeted metabolite profiles with sensory data for the predictive modeling of taste intensities in fermented kimchi - In Min Hwang; Daun Kim; Seul-Gi Jeong; So Yeong Mun; Chang Hee Jeong; Jong-Hee Lee; Ho Myeong Kim (Food Research International, 2026)

Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

Succinic acid as a coordination modulator for DMSO-free low-dimensional red-emitting tin perovskites - Akhil Sreevalsan; Woo Hyeon Jeong; Yifan Yu; Cheong Beom Lee; Gunhee Kim; Jongbeom Kim; Hochan Song; Hong In Jeong; Gyeong Eun Seok; Dong-Won Kang; Myoung Hoon Song; Kyeounghak Kim; et al. (Chemical Engineering Journal, 2026)

Machine learning-based spatiotemporal modeling and health risk assessment of PAHs and metals in an industrial city - Jeong-Tae Ju; Sang-Jin Lee; In-Gyu Cho; Ji Yoon Choi; Taekyu Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Quadruple co-infection with Mycobacterium tuberculosis complex and M. kansasii in a chronically immunosuppressed cat - Sungyoung Choi; Soo-Nyun Choi; Tak Gyeom Lee; Sungweon Ryoo; Ji-Hoon Kwak; Kun-Woo Kim; Tae In Park; Woo-Jin Song; Eun-Joo Lee; Kyu-Shik Jeong (Veterinary Research Communications, 2026)

Part-load operation of the Supercritical CO2 power cycle for Hybrid Micro Modular reactor with control strategy optimization using GAMMA+ - Sungwook Choi; In Woo Son; Jeong Ik Lee (Annals of Nuclear Energy, 2026)

Polymer type drives successional structural and functional organization of plastisphere microbial networks - Kyu-Young Shim; In-Cheol Yeo; Euihyeon Lee; Hyun-Jung Kim; Kang Eun Kim; Jiezhang Mo; Youn-Jung Kim; Chang-Bum Jeong (Marine Environmental Research, 2026)

Allergenicity of edible insect proteins: Cross-reactivity, processing effects, and food safety considerations - Jae Hoon Lee; Ji Yoon Cha; Seonmin Lee; Yea-Ji Kim; Jeong-Heon Kim; Dong Hyun Keum; Hae In Yong; Min Hyeock Lee; Yun-Sang Choi (Food Chemistry, 2026)

Temporally programmed dual-function scaffold with simultaneous cellulose and calcium lactate regeneration for enhanced osteogenesis via lactate-induced OR5AN1 activation - Siphesihle Cassandra Nonjola; Jeong In Kim; Soonchul Lee (Carbohydrate Polymers, 2026)

Application of Fibronectin-Coated Microparticles for Isolation of Human iPSC-Derived MSCs - Jae Hyeok Jang; In Sun Hwang; Ji Seob Kim; Sunjun Lee; Min Hee Moon; Bowon Kim; Seo Jeong Kim; Jongho Choi; Young Her; Soo-Hong Lee; Byung-Hyun Cha (Tissue Engineering and Regenerative Medicine, 2026)
BACKGROUND : Bone marrow–derived MSCs (BMMSCs) are limited by availability, donor variability, and age-related decline, highlighting the need for alternative MSC sources. Induced pluripotent stem cells (iPSCs) offer a scalable solution. This study introduces a novel three-dimensional culture platform based on fibronectin (FN)-coated microparticles to efficiently derive and expand human iPSC-derived MSCs (iMSCs). METHODS : The system utilizes FN-coated non-porous (CytoDex) and porous (CytoPore) microparticles. FN coating efficacy on microparticle was confirmed using Rhodamine-labeled FN and confocal microscope. Base on various molecular cell biological experiment, the utilization of FN-coated CytoDex and CytoPore leverages an expanded surface area to improve iMSCs isolation. The characteristics and cell behaviors of iMSCs generated from FN-coated CytoDex and CytoPore was evaluated by immunophenotype analysis, cell proliferation, and senescence related assays. In vivo tissue regeneration was evaluated by microcomputed tomography and histopathological analyses. RESULTS : The porous microparticle CytoPore significantly enhanced FN coating efficiency, cell attachment, and proliferation compared to CytoDex. FN-coated CytoPore enabled the selective isolation of a high-purity MSC population from spontaneously differentiated iPSCs (SD-iPSCs) by day 7, confirmed by distinct morphology and mesodermal marker expression. The resulting iMSCs exhibited immunophenotypic characteristics comparable to adult MSCs, along with superior proliferative capacity, extended telomere length, and minimal senescence over 10 passages, in contrast to BMMSCs. Furthermore, iMSCs demonstrated effective in vivo tissue regeneration in an osteochondral defect model. CONCLUSION : This novel FN-coated microparticle-based 3D culture platform enables efficient, large-scale production of high-quality iMSCs and holds strong potential for clinical applications in stem cell therapeutics and regenerative medicine.

Effects of Clinostat rotation on stem morphology of Pisum Sativum - Sang-Min Kim; Jung-Hoo Kook; Jeong-In Choi; Oluwasegun Moses Ogundele; Won-Cheol Lee; Hyeon-Tae Kim (Life Sciences in Space Research, 2026)

Physiologically based pharmacokinetic modeling of caffeine in patients with liver cirrhosis: Implications for exposure-guided dose adjustment - Se-In Lee; Chi-Ho Lee; Ji-Hun Jang; Seung-Hyun Jeong (Environmental Toxicology and Pharmacology, 2026)

Dielectric oligonucleotide fragments enable ultralow threshold photomultiplication in infrared quantum dot photodetectors - Yongnam Ahn; Jinwoo Shin; Woo Hyuk Jung; Yong Ho Cho; Minjung Yang; In-Suh Lee; Jaewoo Jeong; Taeho Han; Seoryeon Jeong; Jin Ah Lee; Chae Hyeong Ha; Yoon Jang Chung; et al. (Chemical Engineering Journal, 2026)

Reassembled yeast vacuoles preserve endothelial viability and barrier integrity in an in vitro blood–brain barrier model - Yoon-Young Hwang; Cho-Im Oh; Jin-Pyo Lee; Su-Min Lee; Dae-Young Park; In-Hwan Oh; Tae-rim Kim; Ok Chan Jeong; Ji-Young Ahn; Yang-Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2026)

Heavy metals in carbonated waters and beverages on the South Korean market - Yongcheol Lee; Hyuny Clark-Shim; Min-Su Chang; In-Sook Lee; Yun-Jung Yi; Hyun-Jeong Kim (Food Additives & Contaminants Part B-Surveillance, 2026)

Childhood exposure to traffic-related air pollution and lung function at age 10 years: evidence of nutritional modification in a birth cohort - Yujin Park; Dong-Wook Lee; Choong Ho Shin; Young Ah Lee; Yun Jeong Lee; Dong In Suh; Yun-Chul Hong; Youn-Hee Lim; Bung-Nyun Kim; Johanna Inhyang Kim; Soontae Kim; Kyoung-Nam Kim (International Journal of Hygiene and Environmental Health, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

Unveiling environmental benefits of carbon capture and utilization pathways: Attributional and consequential life cycle assessments - Yujin Baek; Chaehee Gong; Sungil Yun; Jeong In Lee; Wangyun Won (Chemical Engineering Journal, 2026)

Interaction between ethanol and flunitrazepam in rats: Pharmacokinetic mechanisms and toxicological implications - Yejin Kim; Jeong In Seo; Jin Ah Won; Sooyeun Lee; Hye Hyun Yoo (Chemico-Biological Interactions, 2026)

Development of Novel Host-Associated Low-Temperature Probiotics (HALP) Tailored to Aquaculture Applications - Su-Jeong Lee; Young-Sun Lee; Yu-Ri Kim; Mi-Hyeon Jeon; Da-In Noh; Seong-Mok Jeong; Kang-Woong Kim; Eun-Woo Lee; Won Je Jang (Probiotics and Antimicrobial Proteins, 2026)

Development of a Two-Set Multiplex PCR System for Rapid Discrimination of Seven Commercially Important Cuttlefish Species Using COI-Derived SNP Markers - Chun Mae Dong; Mi-Nan Lee; Hee Jeong Park; Hyo Sun Jung; Eun Soo Noh; In Joon Hwang; Jung-Ha Kang; Eun-Mi Kim (Fishes, 2026)
Reliable identification of seafood species is critical for fisheries management and product authentication, especially when morphological characteristics are lost during processing. In this study, a multiplex PCR system was developed to distinguish seven cuttlefish species (six Sepia spp. and Sepiella inermis) commercially distributed in the Korean seafood market. Species identity was first confirmed by amplifying a mitochondrial cytochrome c oxidase subunit I (COI) fragment (~658 bp) using universal primers (LCO1490/HCO2198), showing 99–100% sequence similarity to corresponding GenBank reference sequences. Analysis of genetic variation based on a 530 bp aligned region demonstrated complete interspecific differentiation without shared haplotypes among species. The number of haplotypes per species ranged from 5 to 21, with haplotype diversity values between 0.667 and 1.000. An extended COI fragment (~1200 bp) was further analyzed to identify diagnostic interspecific variation for marker development. Seven diagnostic single-nucleotide polymorphism (SNP) sites were identified and used to design species-specific forward primers with diagnostic nucleotides positioned at the 3′ termini. Distinct amplicons (220–1099 bp) were generated and clearly resolved by agarose gel electrophoresis. Because simultaneous amplification of all seven primer pairs reduced amplification efficiency, the assay was divided into two multiplex sets. Under optimized conditions (56 °C), each species produced a single expected band without cross-amplification. This multiplex PCR system provides a rapid and sequencing-free approach for reliable species discrimination and can be effectively applied to fisheries monitoring and seafood authentication in commercial supply chains.

Calcium carbonate hybrid microcomposite for oral delivery of luteolin, a poorly water-soluble phytocompound - Jung-Ki Hong; Yeji Kang; Seong-Wook Seo; Ji-Su Kong; Gayeong Lee; Chan Hee Lee; Jongwook Jeong; Ee Taek Hwang; In-Soo Yoon (Food Chemistry, 2026)

Probiotic-Derived Strain-Specific Metabolites Ameliorate Metabolic Dysfunction–Associated Steatotic Liver Disease through Modulation of the Gut-Liver Axis - Sang Jun Yoon; Jieun Choi; Sung-Min Won; Jeong Seok Yu; Hee Young Kim; Hyun Chae Joung; In Gyu Park; Jung A Eom; Sang Hak Han; Do Yup Lee; Ki Tae Suk (Probiotics and Antimicrobial Proteins, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Multiplex PCR Assay for the Rapid and Accurate Identification of Three Chionoecetes Species - Chun Mae Dong; Hee Jeong Park; Eun Soo Noh; Seung-Hwan Lee; In Joon Hwang; Jung-Ha Kang; Hyo Sun Jung (Fishes, 2026)
In this study, a multiplex PCR assay was developed for the rapid and accurate identification of three Chionoecetes species (Chionoecetes bairdi, C. opilio, and C. japonicus) available in global seafood markets. The morphological similarity between imported female C. bairdi from Japan and native C. opilio in Korea complicates visual discrimination and raises concerns over potential mislabeling. To address this issue, mitochondrial cytochrome c oxidase subunit I (COI) gene sequences were analyzed to identify species-specific SNPs, and primers were designed accordingly. Singleplex PCR confirmed species-specific amplification among the three target species, and the optimal annealing temperature was determined. The multiplex PCR simultaneously amplified distinct fragments of 598 bp (C. bairdi), 401 bp (C. opilio), and 194 bp (C. japonicus), with no nonspecific amplification or primer–dimer formation. Sensitivity testing revealed a detection limit of 0.01 ng/µL for all three species, defined as the lowest DNA concentration at which species-specific bands were consistently observed in at least two out of three replicates. These results demonstrate that the developed multiplex PCR is a reliable, rapid, and cost-effective tool for accurate species identification, supporting sustainable resource management, preventing seafood fraud, and ensuring safe distribution in both Korea and global seafood markets.

Standardized olive pomace juice ameliorates scopolamine-induced cognitive decline in C57BL/6 mice via AMPKα-SIRT1-PGC1α and CREB-BDNF-TrkB signaling pathways - Ye-Lim You; Ha-Jun Byun; Namgil Kang; Min Soo Lee; Jeong-In Lee; Ilbum Park; Hyeon-Son Choi (Food Bioscience, 2026)

Achieving BT.2020 red emission with narrowband deep-red iridium complexes in OLEDs - Gyeong Seok Lee; Woo Jin Jeong; Huanyu Zhou; Hyun-Wook Kim; Da In Kim; Kwan-Nyeong Kim; Dong-Hyeok Kim; Thi Na Le; Seungyeon Cho; Jongchan Kim; Tae-Woo Lee; Yun-Hi Kim (Chemical Engineering Journal, 2026)

A single urine test-based SERS–AI–BAM for on-site multiple cancer diagnosis and metabolite profiling - Hyo Jeong Seo; Jun Young Kim; Vo Thi Nhat Linh; Boyou Heo; Jun-Young Yang; Rowoon Park; In Woong Han; Sung-Gyu Park; Min-Young Lee; Samjin Choi; Ho Sang Jung (Chemical Engineering Journal, 2026)

Tissue region-dependent differential responses of fruit quality attributes, mineral nutrients, and targeted major metabolites in blossom-end rot of paprika fruit - Si-Eun Byeon; Hyowon Park; Sangyo Jeong; Jiwon Park; Theint Thandar Latt; Jinhee Lee; In Geun Hwang; Jinwook Lee (Horticulture, Environment, and Biotechnology, 2026)

Molecular biomarkers associated with environmental naphthalene exposure in the respiratory system - Hye-Jeong Han; Amartuvshin Baasankhuu; Bogun Kim; Angela Astrid Sekar Prameswari; Karina Kalani; Paolo Panza; Sangwoo Lee; Woo-Keun Kim; In-Geol Choi; Cheol-Hee Kim; Hyun-Taek Kim (Science of The Total Environment, 2026)

Flame-constructed spinel Fe-Ni-O nanoparticles-on-nanosheet superstructures for scalable and durable hydrogen production - Jin Sil Kim; Sung Won Hwang; Yoo Jae Jeong; Runfa Tan; Ha Min Lee; Arumugam Sivanantham; In Sun Cho (Chemical Engineering Journal, 2026)

Enhancing CO2-to-CH4 conversion efficiency of TiO2 through synergistic morphology tuning, defect engineering, and heterojunction formation - Dongyun Kim; Kyuseok Lee; Young Ho Park; Junho Lee; Jeonghyeon Lee; Chaelin Shin; Hyeonjong Jeong; Chang-Hee Cho; G. Murali; Seung Jun Lee; Insik In; Su-Il In (Chemical Engineering Journal, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Disturbance of benthic topography and macrofauna community by sand mining in EEZ of the South Sea of Korea - Dong-U Kim; Changkeun Lee; Su In Kim; Seong Woon Jeong; Taeha Kim; Eun Pyo Lim; Soonwoo Lee; Soonyoung Wang; Seong Eun Kim; Jong Seong Khim; Ho Kyung Ha (Regional Studies in Marine Science, 2025)

Integrated VOC and non-VOC profiling for stage-specific quality assessment of kimchi fermentation using LC-MS/MS and GC-IMS - Ji Young Jeong; Min Ji Kim; Hyun-Sung Kim; Jong-Hee Lee; In Min Hwang (Food Chemistry, 2025)

Serine protease–viscoelastic polysaccharide interaction in inorganic CaCO3: Enhanced thermal stability for efficient enzyme particulation via immobilization - Soyoon Baek; Chan Hee Lee; Dain Kim; Jinhee Jeong; In Ki Hong; Seunghee Bae; Ee Taek Hwang (Carbohydrate Polymers, 2025)

FOXO3a upregulates DNA repair activities by transcriptional activation of target genes and provides the resistance to gamma radiation and the extension of lifespan in mouse - Gozde Inci; Madhuri Shende Warkad; Beom-Goo Kang; Sung-Ok Kim; Na-Kyung Lee; Jee-In Heo; Seong-Hoon Park; Jeong-Hyun Kim; Hong-Jun Kang; Chae-Ha Kim; Byung-Hak Kim; Sang-Jae Park; et al. (Biogerontology, 2025)

Modulating kimchi taste and fermentation with Latilactobacillus sakei, Leuconostoc mesenteroides, and Weissella koreensis starters - So Yeong Moon; Chang Hee Jeong; In Min Hwang; Daun Kim; Mo Eun Lee; Seul-Gi Jeong; Ho Myeong Kim (Food Research International, 2025)

Hybrid W-MgF2/graphene photothermal membrane for efficient solar-driven desalination - Ga Eun Lee; Jinsoo Cho; In-Young Jung; Da Seul Kim; Seok Joon Kwon; Won Jun Choi; Kyung Guen Song; Hak Ki Yu; Jeong Min Baik (Desalination, 2025)

3D liver model for assessing immune-mediated hepatotoxicity from biopharmaceutical risks - Mi-lang Kyun; Duhyeon Park; Hyewon Jung; Ji Hyeon Ryu; Inhye Kim; Seo Yule Jeong; Jeongha Kim; Minseong Jo; Ji-In Kwon; Ju-Kang Kim; Dahong Kim; Su A. Park; et al. (Chemical Engineering Journal, 2025)

Enhanced oral bioavailability of pranlukast by preparing amorphous solid dispersion via hot-melt extrusion - Dong-Hyeon Ha; Eun-Sol Ha; Heejun Park; Seon-Kwang Lee; Ji-Su Jeong; Hui-Taek Kang; Kyu-Tae Kang; In-hwan Baek; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2025)

Effect of permanent magnetic fields on freezing characteristics of agar gel and potato - In-U Jeong; Chang Joo Lee; Jin Hong Mok; Taiyoung Kang (International Journal of Refrigeration, 2025)

Transcriptomic analysis revealed the adaptations of Latilactobacillus sakei to the cold conditions of kimchi fermentation - Min Ji Kim; Ji Young Jeong; Hyun-Sung Kim; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Research International, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Calcium-Rich Steel Slag as a Reactive Capping Material: Effects on Hydraulic Conductivity and Nutrient Attenuation in Cohesive Intertidal Sediments - Hee-Eun Woo; Valianto Rojulun Afif; Seongsik Park; Maheshkumar Prakash Patil; Ilwon Jeong; In-Cheol Lee; Jong-Oh Kim; Kyunghoi Kim (Journal of Marine Science and Engineering, 2025)
Fine-grained intertidal sediments are typically characterized by low hydraulic conductivity and high nutrient loads, conditions that hinder biogeochemical recovery and exacerbate eutrophication. This study examined the feasibility of calcium-rich steel slag (SS) as a multifunctional capping material for improving both physical and chemical properties of cohesive sediments. Short-term (24 h) column experiments with two slag dosages (25 g and 50 g) revealed that the higher dosage (SS50) increased sediment hydraulic conductivity by 113.2%, likely through Ca2+-mediated flocculation and enhanced pore connectivity. Phosphate (PO4-P) in pore water decreased by up to 64.1%, and effluent dissolved inorganic nitrogen (DIN) declined by 62.8%, indicating combined effects of Ca-driven precipitation, adsorption, and enhanced flushing. However, SS addition also raised pore water pH (to 11.8) and lowered redox potential, leading to transient phosphate release at the effluent boundary under reducing conditions. Cation analysis confirmed Ca2+ stability and Na+ reduction, suggesting improved sediment structural integrity. The results suggest that steel slag is a promising reactive capping material capable of enhancing permeability and controlling nutrient release in cohesive coastal sediments, yet further investigation into long-term ecological effects and dosage optimization is necessary.

Visible light-driven selective redirection of phenolic carbon in heterogeneous Fenton-like reaction - Youn-Jun Lee; Prakash Govindaraj; Yoo Jae Jeong; Runfa Tan; In Sun Cho; Seong-Jik Park; Hern Kim; Chang-Gu Lee; Pedro J.J. Alvarez (Water Research, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Dissecting the role of hydrogen pumping by rhenium oxide in enhancing the dehydrogenation of perhydro-dibenzyltoluene on Pt/Al2O3 - Ji Soo Jang; Min-Woo Lee; Seok-Ho Lee; Eun-Suk Jeong; Tae In Park; Kwan-Young Lee (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Evaluating ripeness in post-harvest stored kiwifruit using VIS-NIR hyperspectral imaging - Jeong-Eun Lee; Min-Jee Kim; Bo-Yeong Lee; Lee Jong Hwan; Ha-Eun Yang; Moon S. Kim; In Geun Hwang; Cheon Soon Jeong; Changyeun Mo (Postharvest Biology and Technology, 2025)

Garlic as a modulator of bacterial dynamics and metabolite profiles in kimchi fermentation - Min Ji Kim; Sera Jung; Hyun-Sung Kim; Ji Young Jeong; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Bioscience, 2025)

Seasonal dynamics of picocyanobacteria and bloom-forming cyanobacteria in Daechung Reservoir, Korea - Hye Jeong Choi; In-Chan Choi; So Hyun Cho; Eun-mi Hong; Jay Jung Lee (Paddy and Water Environment, 2025)

Immunomodulation Effects of Porcine Cartilage Acellularized Matrix (pCAM) for Osteoarthritis Treatment - Ji Seob Kim; Hyeon Jae Kwon; In Sun Hwang; Young Hwa Lee; Kyung-Noh Yoon; Hee-Woong Yun; Jae-Hyeok Jang; Seo Jeong Kim; Zhoodatova Aiana; Seungwoo Kim; Minhee Moon; Bongki Kim; et al. (Tissue Engineering and Regenerative Medicine, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Modulation of fermentation dynamics in kimchi using Leuconostoc mesenteroides starter - Min Ji Kim; Ji Young Jeong; In Min Hwang; Jong-Hee Lee (Food Bioscience, 2025)

Defect-engineered black indium oxide: A high-performance photothermal material for solar-driven water purification - Runfa Tan; Tatachari Santhanagopalan Shridharan; Jong Ho Lee; Mukkath Joseph Josline; Jae Yeong Lee; Jong Seong Bae; Arumugam Sivanantham; Yoo Jae Jeong; Jae-Hyun Lee; Sangwook Lee; In Sun Cho (Desalination, 2025)

Nano-TiO2 removal using jellyfish extracts and an assessment of aquatic toxicity - In Hae Park; Joo Eun Shim; Hyesoo Lee; Ki Heon Jeong; Min-Kyeong Yeo (Molecular & Cellular Toxicology, 2025)

Development of advanced polyacrylonitrile fiber-based adsorbents for heavy metal ion removal through electron beam irradiation followed by amination - Minho Son; Jong-Seok Park; Sung-In Jeong; Byoung-Min Lee; Jae-Hak Choi; Joon-Pyo Jeun (Journal of Water Process Engineering, 2025)

Pheromone biosynthesis activating neuropeptide induces attractant production in female adults of Bemisia tabaci (MED) - Wook Hyun Cha; In Hong Jeong; Dae-Weon Lee (Journal of Asia-Pacific Entomology, 2025)

Development of a comprehensive air risk index and its application to high spatial-temporal health risk assessment in a large industrial city - Sang-Jin Lee; In-Gyu Cho; Ho-Young Lee; Jeong-Tae Ju; Hye-Jung Shin; Sung-Deuk Choi (Environmental Pollution, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Conjugated polymer of Multi-arm-PEG and dimethylsiloxane (CPMD) for the effective transdermal delivery of deoxycholic acid for fat reduction - Hwajun Jeong; Hye-Lin Kim; Harim Kim; Min-Suk Lee; Jae-Min Cho; Chan Lee Park; Hyo In Kim; Jinbong Park; Dokyoung Kim (Chemical Engineering Journal, 2025)

Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Ju-Wook Baek; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Sokjin Hong; Dae In Lee; Jae Seong Lee (Frontiers in Marine Science, 2025)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O 2 m –2 d –1 , and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O 2 m –2 d –1 . The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m -2 d –1 , and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m –2 d –1 , and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m –2 d –1 for nitrogen, from 0.02 to 0.05 mmol m –2 d –1 for phosphate, and from 6.72 to 9.11 mmol m –2 d –1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.

Single oral toxicity assessment and phytochemical analysis of the Ficus erecta Thunb. Leaves extract - Yu Jin Kim; Mee-Young Lee; Hyun Ji Park; Eunjin Sohn; Woo-Young Jeon; Sae-Rom Yoo; In Suk Choi; Joo-Hwan Kim; Soo-Jin Jeong (Toxicon, 2025)

Introducing Cu2O (111) phase on Cu(OH)2 nanorods integrated Pd-cocatalyst for boosting acetone selectivity via photoelectrochemical CO2RR - Periyayya Uthirakumar; Dasom Kim; Vandung Dao; Chen Kai; Changmin Yun; Youn Jeong Jang; In-Hwan Lee (Environmental Research, 2025)

Role of Rab proteins in PFOA-induced changes in boar sperm motility and capacitation - Seung-Ik Jang; Jae-Hwan Jo; Claudine Uwamahoro; Eun-Ju Jung; Woo-Jin Lee; Jeong-Won Bae; Sangsu Shin; Sang In Lee; Myoung Ok Kim; Joonho Moon; Woo-Sung Kwon (Reproductive Toxicology, 2024)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

Genetic dissection of resistance to Phytophthora sojae using genome-wide association and linkage analysis in soybean [Glycine max (L.) Merr.] - Hee Jin You; Ik Hyun Jang; Jung-Kyung Moon; In-Jeong Kang; Ji-Min Kim; Sungtaeg Kang; Sungwoo Lee (Theoretical and Applied Genetics, 2024)

Lelliottia wanjuensis sp. nov. Isolated from Korean Lettuce in Wanju, South Korea - Jiyeon Lee; Eewon Tai; Sunyoung Jeong; Ile Kim; Bo-Eun Kim; Myeong-In Jeong; Kwang-Kyo Oh; Natalia Biere; Charles M. A. P. Franz; Gyu-Sung Cho (Current Microbiology, 2024)
Ten Gram stain-negative, oxidase-negative, catalase-positive, rod-shaped strains were isolated from lettuce in the city Wanju in South Korea. Comparative 16S rRNA gene analysis and multilocus sequence analysis indicated that the strains grouped closely together with all other Lelliottia ( L .)-type strains. The average nucleotide identity (ANI) comparisons of the isolates showed a high relationship between the strains, as the ANI values of all strains ranged from 91.01 to 91.31% when compared to the L. jeotgali- type strain PFL01 T . All isolates showed the highest genomic DNA sequence similarity to the L. jeotgali PFL01 T strain at 43.3% when compared with digital DNA–DNA hybridization (dDDH). Strain V104_15 T of the proposed novel Lelliottia species showed 91.2% and 43.3% similarity with the most closely related L. jeotgali PFL01 T -type strain in the ANI and dDDH comparisons, respectively. Strain V104_15 T could not grow at 45 °C and 7% NaCl, while L. jeotgali PFL01 T strain could grow at both these conditions. Strain V104_15 T showed ß -glucosidase activity but not α-glucosidase activity, while the L. jeotgali PFL01 T strain was α -glucosidase positive but ß-glucosidase negative. The major cellular fatty acids of strain V104_15 T were C 16:0 and cyclo-C 17:0 including summed features. The mol % G + C content of the genomic DNA of strain V104_15 T was 55.74%. Phenotypic and biochemical characteristics, as well as the phylogenomic analysis indicated that the strain V104_15 T represents a novel species of the genus Lelliottia , for which the name Lelliottia wanjuensis sp. nov. is proposed. The type strain is V104_15 T (= LMG 32996 T = DSM 115585 T ).

Daily and seasonal changes of sap flow in Gamhong apple cultivar and estimate the tree-level transpiration using Penman-Monteith reference evapotranspiration - Narayan Bhusal; Louis S. Santiago; Joncheon Lee; Sanghak Jeong; In Hee Park; Byeong-Ho Choi; Hun-Joong Kweon; Su-Gon Han; Tae-Myung Yoon (South African Journal of Botany, 2024)

A new neo-lignan from culture broth of Phellinus linteus and its dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Nationwide evaluation of microplastic properties in municipal wastewater treatment plants in South Korea - Jae-Ho Lee; So-Jeong Cheon; Chang-Soo Kim; Soo-Hyun Joo; Ki-In Choi; Dong-Hwan Jeong; Soo-Hyung Lee; Jeong-Ki Yoon (Environmental Pollution, 2024)

Olaparib synergically exacerbates the radiation-induced intestinal apoptosis in mice - Sohee Jeong; Jeongmin Lee; Jun Hong Park; Yeonghoon Son; Hae-June Lee; Changjong Moon; In Sik Shin; Joong Sun Kim; Sohi Kang (Molecular & Cellular Toxicology, 2024)

T cell receptor clonotype in tumor microenvironment contributes to intratumoral signaling network in patients with colorectal cancer - In Hye Song; Seung-been Lee; Byung-Kwan Jeong; Jungwook Park; Honggeun Kim; GunHee Lee; Su Min Cha; Heejae Lee; Gyungyub Gong; Nak-Jung Kwon; Hee Jin Lee (Immunologic Research, 2024)

Harnessing wood bottom ash for efficient arsenic removal from wastewater: Adsorption mechanisms and process optimisation - Jae-In Lee; Yohan Jeong; Youn-Jun Lee; Chang-Gu Lee; Seong-Jik Park (Chemosphere, 2024)

Nationwide monitoring of legacy and emerging persistent organic pollutants and polycyclic aromatic hydrocarbons along the Korean coast - Gyojin Choo; Sol Choi; In-Seok Lee; Jeong-Eun Oh (Marine Pollution Bulletin, 2024)

Ultrathin silica-encapsulated perovskite nanocrystals for high color purity mechanoluminescence - Kyung Sik Yoo; Hong In Jeong; Sujoy Bandyopadhyay; Seo-Jin Ko; Dong-Won Kang; Jihoon Lee; Hyosung Choi (Chemical Engineering Journal, 2024)

Enhancing acetaminophen removal through persulfate activation with ZnCl2-SPI biochar: A study on reactive oxygen species contribution according to acetaminophen concentration - Heejin Yang; Gyu-Ri Choi; Yoo Jae Jeong; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Chemical Engineering Journal, 2024)

Ultrathin Two-Dimensional Ordered Porous Carbon Host with Atomically Dispersed Electrocatalytic Sites toward High Volumetric Energy Lithium-Sulfur Battery - Won-Gwang Lim; Minkyeong Ban; Kyu In Shim; Jinkyu Park; Seongbeen Kim; Seongseop Kim; Seoa Kim; Cheol-Young Park; Jeong Woo Han; Jinwoo Lee (Chemical Engineering Journal, 2024)

Design and Simulation-Based Validation of an AI Model for Predicting Grab-Type Ship Unloader Operation Data - Ga-Eun Jung; Woo-Hee Jeong; Seok-Ju Lee; Jae-In Lee; Tae-Won Kim; Hae-Jin Sung (Journal of Marine Science and Engineering, 2024)
Along with seaports automation, there is growing interest in the automation of Grab-Type Ship Unloader (GTSU) that unloads coal and iron ore from bulk carriers. Autonomous unloading operations of GTSU offer the potential for significant productivity improvement and cost savings. In this paper, an AI model trained with manual operation data was designed for GTSU automation operation, and the AI model was verified through the equation-of-motion-based GTSU operation simulator. The operation data of hoist, grab, and trolley were predicted by training the designed AI model with the manual operation data of GTSU. Before applying the predicted data to the actual equipment, the predicted driving data was verified using the equation-of-motion-based GTSU operation simulator. The AI prediction model was designed using the Multi-Layer Perception network, a type of artificial neural network. The AI prediction model was evaluated with the Mean-Squared Error indicator, and the validation loss was found to be less than 0.02. In addition, verification of the prediction data was performed using the GTSU dynamics-based simulator. The Mean Relative Error was up to 0.50, and the R2 score value exceeded 0.92, indicating that the model is effective in predicting operation data. The proposed AI prediction model will be effectively utilized to implement a fully automated unloading system.

Exploratory data analysis of the correlation between bioactive components in various tea extracts and the digestive function in vitro - Kang-Woo Lee; In-Su Na; Dong-Ho Lee; Jin-Woo Kim; Na-Yeon Lee; Jin-Oh Chung; Hyun Woo Jeong; Jonghee Sohn; Wan-Gi Kim; Soon-Mi Shim (Food Bioscience, 2024)

Mutational analysis of pig tissue factor pathway inhibitor α to increase anti-coagulation activity in pig-to-human xenotransplantation - Chang-Hee Lee; Hyeon Jeong Lee; Si-Won Park; Jiyoon Shin; Seok-Jin Kang; In-Byung Park; Hyun Kyung Kim; Taehoon Chun (Biotechnology Letters, 2024)

Relationship between rheological properties, sensory perception, and overall acceptability of thickened liquids for dysphagia in young and old healthy individuals - Yong Gi Chun; Yun Jeong Kim; In Young Lee; Eun Young Jeon; Bum-Keun Kim (Food Research International, 2024)

A heterostructured ternary transition metal oxide composite as an efficient electrocatalyst for the hydrogen evolution reaction - Soo Hong Lee; Seunghwan Jo; Jeong In Jeon; Jung Inn Sohn; John Hong (Journal of Environmental Chemical Engineering, 2024)

Evaluation of Initial Fire Extinguishing System for Marine ESS - Seung-Yul Lee; In-Chul Park; Jeong-Hoon Park; Hyo-Seok Jung (Journal of Marine Science and Engineering, 2024)
A fire in a marine energy storage system (ESS) has a high risk because of the special situation of the sea compared with land systems. To mitigate serious damage in the event of a fire in marine ESSs, initial suppression of the fire is extremely important. In this study, a unit module-based fire extinguishing system was constructed for the initial suppression of an ESS fire, and a unit module fire suppression test was conducted. In addition, multiple modules were constructed to evaluate the impact of unit module fire suppression on adjacent modules. Novec 1230 and F-500, which are adaptable to ESS fire control, were used as extinguishing agents. The fire suppression test results showed that both extinguishing agents could effectively suppress the ESS fire in the initial stage using the proposed fire extinguishing system. The results of this study will contribute to the development of maritime safety protocols and practical measures for reinforcing preparation for ESS-related fire accidents.

Highly visible-light-active sulfur and carbon co-doped TiO2 (SC-TiO2) heterogeneous photocatalysts prepared by underwater discharge plasma - Ha-Rim An; Chaehun Lim; Chung Gi Min; Byoungchul Son; Chang-Yeon Kim; Ji-In Park; Jong Pil Kim; Yesul Jeong; Jiwon Seo; Moonsang Lee; Jihyang Park; Young-Seak Lee; et al. (Chemosphere, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Three undescribed dimeric ferulates from the culture broth of Phellinus linteus and their dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Won-Gi Seo; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Mechanochemical activation of silicon photothermal material for efficient interfacial solar desalination and wastewater purification - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Jong Ho Lee; Seo Yeong Hong; Yoo Jae Jeong; Seong Sik Shin; In Sun Cho (Chemical Engineering Journal, 2024)

Low-dose-rate gamma radiation aggravates titanium dioxide nanoparticle-induced lung injury in mice - Sohi Kang; Hae-June Lee; Yeonghoon Son; Min Ji Bae; Wol Soon Jo; Jun Hong Park; Sohee Jeong; Changjong Moon; In-Sik Shin; Chang Geun Lee; Joong Sun Kim (Molecular & Cellular Toxicology, 2024)

Graphitic-carbon-nitride-hydrophilicity-dependent photocatalytic degradation of antibiotics with different log Kow - Jong-Min Lee; Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Eun Hea Jho; Seong-Jik Park; Chang-Gu Lee (Chemosphere, 2024)

A comparison of the nutritional quality of ready-to-cook meals and conventional home-cooked meals in Korea - Eunji Choi; Sung-Won Yoon; Jung-Ah Shin; In-Hwan Kim; Jeehye Sung; Jang-Hyuk Ahn; Hyun-Jeong Kim; Dong Won Seo; Sam-Pin Lee; Jo-Won Lee; Bo Kyung Moon; Sojung Kim; et al. (International Journal of Gastronomy and Food Science, 2024)

Physicochemical characterization and environmental stability of a curcumin-loaded Pickering nanoemulsion using a pea protein isolate-dextran conjugate via the Maillard reaction - Yun Jeong Kim; Hae In Yong; Yong Gi Chun; Bum-Keun Kim; Min Hyeock Lee (Food Chemistry, 2024)

Combination approach of paired starter culture and lactic acid on inhibiting autochthonous lactic acid bacteria for extending kimchi shelf life - Chang Hee Jeong; Hye In Ko; Mo Eun Lee; Sung-Gi Min; Mi-Ai Lee; Tae-Woon Kim (Food Control, 2024)

High-performance interfacial water evaporation of black TiO2-x with high-concentration bulk oxygen vacancies - Myeongjun Ji; Jeong Hyun Kim; Hee Yeon Jeon; Seungheon Han; Dong Hoon Lee; Young-In Lee (Chemical Engineering Journal, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Bioconversion of citrus waste into mucic acid by xylose-fermenting Saccharomyces cerevisiae - Deokyeol Jeong; Sujeong Park; Grace Evelina; Suhyeung Kim; Heeyoung Park; Je Min Lee; Sun-Ki Kim; In Jung Kim; Eun Joong Oh; Soo Rin Kim (Bioresource Technology, 2024)

Considering the Chemical Components of Particulate Matter 2.5 for Assessing Its Health Risks to Residents near the Ansan/Siheung and Ulsan Industrial Complexes - Ji-Yun Jung; Shin-Young Park; Jeong-In Jeon; Hye-Won Lee; Sung-Won Yoon; Cheol-Min Lee (Water, Air, & Soil Pollution, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Perfluorooctanoic acid suppresses sperm functions via abnormal Protein Kinase B activation during capacitation - Seung-Ik Jang; Jae-Hwan Jo; Eun-Ju Jung; Woo-Jin Lee; Ju-Mi Hwang; Jeong-Won Bae; Sangsu Shin; Sang In Lee; Myoung Ok Kim; Woo-Sung Kwon (Reproductive Toxicology, 2024)

Characterization of naturally occurring radioactive material dynamics in community water systems using groundwater from Ganghwa Island, Republic of Korea - Eunhyung Lee; Do-Hwan Jeong; Youn-Tae Kim; Inkyu Shin; Yu-Yeon Jeong; Jeong-In Kim; Minkyeong Lee; Hyun-koo Kim; Soo-Hyung Lee; MoonSu Kim (Journal of Hydrology, 2024)

TRIAD method to assess ecological risks of contaminated soils in abandoned mine sites - Dokyung Kim; Jin Il Kwak; Tae-Yang Lee; Lia Kim; Haemi Kim; Sun Hwa Nam; Wonjae Hwang; June Wee; Yong Ho Lee; Songhee Kim; Ji-In Kim; Sunhee Hong; et al. (Journal of Hazardous Materials, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Diesel particulate matter aggravates cyclophosphamide-induced testicular toxicity in mice via elevating oxidative damage - Woong-Il Kim; Je-Oh Lim; So-Won Pak; Se-Jin Lee; Yea-Gin Yang; In-Sik Shin; Changjong Moon; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2024)

Improving spray performance of vehicle disinfection systems in livestock farms using computational fluid dynamics analysis - Lak-yeong Choi; Se-yeon Lee; Jinseon Park; Se-woon Hong; Kehinde Favour Daniel; Hyo-hyeog Jeong; In-bok Lee (Computers and Electronics in Agriculture, 2023)

Dynamic response of bacterial communities to Microcystis blooms: A three-year study - Ve Van Le; Mingyeong Kang; So-Ra Ko; Seonah Jeong; Chan-Yeong Park; Jay Jung Lee; In-Chan Choi; Hee-Mock Oh; Chi-Yong Ahn (Science of The Total Environment, 2023)

Performance comparison of photodynamic antimicrobial chemotherapy with visible-light-activated organic dyes: Rose bengal, crystal violet, methylene blue, and toluidine blue O - Jae Hak Shin; Sang Bin Jeong; In Ho Kim; Seung Yeon Lee; Gi Byoung Hwang; Inyong Park; Ki Joon Heo; Jae Hee Jung (Environmental Research, 2023)

Development of an In Vitro Model for Inflammation Mediated Renal Toxicity Using 3D Renal Tubules and Co-Cultured Human Immune Cells - Mi-lang Kyun; Tamina Park; Hyewon Jung; Inhye Kim; Ji-In Kwon; Seo Yule Jeong; Myeongjin Choi; Daeui Park; Yu Bin Lee; Kyoung-Sik Moon (Tissue Engineering and Regenerative Medicine, 2023)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

Molecular, biochemical, and toxicological characterization of two acetylcholinesterases from the Western flower thrips, Frankliniella occidentalis - Jong Hyeok Lee; In Hong Jeong; Dong Woon Lee; Si Hyeock Lee; Kyungjae Andrew Yoon (Pesticide Biochemistry and Physiology, 2023)

Field experiments on chemical and biological changes of thin-layer oyster shells capping sediments in dense aquaculture area - Hee-Eun Woo; Ilwon Jeong; Jong-Oh Kim; Young-Ryun Kim; In-Cheol Lee; Kyunghoi Kim (Environmental Research, 2023)

The inhibitory mechanism of humic acids on photocatalytic generation of reactive oxygen species by TiO2 depends on the crystalline phase - Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Chang-Gu Lee; Seong-Jik Park; Pedro J.J. Alvarez (Chemical Engineering Journal, 2023)

Microplastic contamination in groundwater of rural area, eastern part of Korea - Eunju Jeong; Young-In Kim; Jin-Yong Lee; Maimoona Raza (Science of The Total Environment, 2023)

Effect of pulsed electric field pretreatment on mass transfer during hot air drying: Drying and rehydration properties of sweet potato - Si-Yoen Kim; Ui-Chan Jeong; Hye-In Ju; Seho Jeong; Dong-Un Lee (Innovative Food Science & Emerging Technologies, 2023)

Development of high-performance organic photodetectors by understanding origin of dark current density with synthesis of photoconductive polymers - WonJo Jeong; Jinhyeon Kang; Dongchan Lee; Cheol Shin; Hyungju Ahn; Chan So; Jong Ho Won; Dae Sung Chung; Shinuk Cho; In Hwan Jung (Chemical Engineering Journal, 2023)

Detection of microplastic traces in four different types of municipal wastewater treatment plants through FT-IR and TED-GC-MS - Jae-Ho Lee; Min-Jung Kim; Chang-Soo Kim; So-Jeong Cheon; Ki-In Choi; Juyang Kim; Jaehak Jung; Jeong-Ki Yoon; Soo-Hyung Lee; Dong-Hwan Jeong (Environmental Pollution, 2023)

First report on natural infection of Nepenthes alata by pepper mild mottle virus in Korea - Ga-Eun Lee; Hae-Jun Kim; In-Sook Cho; Rae-Dong Jeong (Journal of Plant Pathology, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

First report of natural infection of Malva vertillata by turnip mosaic virus in Korea - Hyo-Jeong Lee; In-Sook Cho; Rae-Dong Jeong (Journal of Plant Pathology, 2023)

Development and application of a reverse transcription droplet digital PCR assay for detection and quantification of Plantago asiatica mosaic virus - Hyo-Jeong Lee; Sena Choi; In-Sook Cho; Ju-Yeon Yoon; Rae-Dong Jeong (Crop Protection, 2023)

Simulation of contamination and elimination of Escherichia coli, Listeria monocytogenes, and Murine norovirus 1 (MNV-1) from the washing process when handling of potatoes - Hyojin Kwon; Zhaoqi Wang; Hyelim Gu; Sumin Hwang; Youngmin Hwang; Jihoon An; Dong-Un Lee; Myeong-In Jeong; Changsun Choi (International Journal of Food Microbiology, 2023)

Coupling of δ13C and δ15N to understand soil organic matter sources and C and N cycling under different land-uses and management: a review and data analysis - Hyun-Jin Park; Nuri Baek; Sang-Sun Lim; Young-Jae Jeong; Bo-Seong Seo; Jin-Hyeob Kwak; Sang-Mo Lee; Seok-In Yun; Han-Yong Kim; Muhammad A. Arshad; Woo-Jung Choi (Biology and Fertility of Soils, 2023)

Development and validation of an air recirculated ventilation system, Part 1: Application of system in a pig farm and evaluation of pig productivity during winter - Jun-gyu Kim; In-bok Lee; Andre Aarnink; Bong-joo Lee; Deuk-young Jeong; Hyo-hyeog Jeong; Se-han Kim; Bong-kuk Lee; Dong-kyu Lee (Biosystems Engineering, 2023)

Development and validation of an air recirculated ventilation system, Part 2: Evaluation of pig productivity in spring and summer seasons including examination of cooling methods - Jun-gyu Kim; In-bok Lee; Deuk-young Jeong; Se-jun Park; Jeong-hwa Cho; Rack-woo Kim (Biosystems Engineering, 2023)

Microplastic contamination in groundwater on a volcanic Jeju Island of Korea - Young-In Kim; Eunju Jeong; Jin-Yong Lee; Rogers Wainkwa Chia; Maimoona Raza (Environmental Research, 2023)

Unveiling reactive origin through the in situ 2D core–shell formation, Ni(CN)2@Ni2P, derived from Hofmann-type MOF for water oxidation - Jiwon Kim; Hyung Wook Choi; Jongseok Kim; Jung Hyeon Yoo; Dong In Jeong; Ui Young Lee; Hyuk Choi; Bong Kyun Kang; Ki-Seok An; Hyun You Kim; Dae Ho Yoon (Chemical Engineering Journal, 2023)

Determination of the optimal location and the number of sensors for efficient heating, ventilation, and air conditioning system operation in a mechanically ventilated pig house - Uk-Hyeon Yeo; Sang-Yeon Lee; Se-Jun Park; Jun-Gyu Kim; Deuk-Young Jeong; Cristina S. Decano-Valentin; Rack-Woo Kim; In-Bok Lee (Biosystems Engineering, 2023)

Depositional history of the subaqueous delta off the southeastern coast of Korea during the post-glacial period - Eun-Je Jeong; Jang-Jun Bahk; In-Kwon Um; Gwang-Soo Lee; Boyeon Yi (Marine Geology, 2023)

Facile synthesis of N vacancy g-C3N4 using Mg-induced defect on the amine groups for enhanced photocatalytic •OH generation - Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Seong-Jik Park; Chang-Gu Lee; Pedro J.J. Alvarez (Journal of Hazardous Materials, 2023)

Rational design of composite supporting electrolyte required for achieving high performance aqueous organic redox flow battery - Wonmi Lee; Kyu In Shim; Gyunho Park; Jeong Woo Han; Yongchai Kwon (Chemical Engineering Journal, 2023)

Understanding protein digestion in infants and the elderly: Current in vitro digestion models - Seonmin Lee; Kyung Jo; Hyun Gyung Jeong; Yun-Sang Choi; Hae In Yong; Samooel Jung (Critical Reviews in Food Science and Nutrition, 2023)

Estimation of ventilation rate in a piglet house considering ventilation system characteristics - Young-bae Choi; Jun-gyu Kim; Jeong-hwa Cho; Sang-yeon Lee; Se-jun Park; Cristina Decano-Valentin; Deuk-young Jeong; In-bok Lee (Biosystems Engineering, 2023)

Characteristics of pork emulsion gel manufactured with hot-boned pork and winter mushroom powder without phosphate - Hyun Gyung Jeong; Kyung Jo; Seonmin Lee; Hae In Yong; Yun-Sang Choi; Samooel Jung (Meat Science, 2023)

Desulfurization characteristics of limestone slurry with added organic acid - Ji Eun Jeong; In Ah Cho; Chang-Yong Lee (Fuel, 2023)

Recycling of minerals with acetate separation in biological syngas fermentation with an electrodialysis system - Jae-Hun Kim; Mungyu Lee; Hoyoung Jeong; Songju Ko; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2023)

Natural Variations in the Benthic Environment and Bacterial Communities of Coastal Sediments around Aquaculture Farms in South Korea - Maheshkumar Prakash Patil; Ilwon Jeong; Hee-Eun Woo; Jong-Oh Kim; Dae In Lee; Kyunghoi Kim (Indian Journal of Microbiology, 2023)

High-pressure induced structural modification of porcine myofibrillar protein and its relation to rheological and emulsifying properties - Min Hyeock Lee; Hae In Yong; Yun Jeong Kim; Yun-Sang Choi (Meat Science, 2023)

A highly efficient and versatile genetic engineering toolkit for a methanotroph-based biorefinery - Jiyeong Jeong; Tae Hyun Kim; Nulee Jang; Minji Ko; Seong Keun Kim; Ji In Baek; Georgii Emelianov; Eugene Rha; Kil Koang Kwon; Haseong Kim; Eun Yeol Lee; Dae-Hee Lee; et al. (Chemical Engineering Journal, 2023)

Identification of novel missense mutation related with non-syndromic sensorineural deafness, DFNA11 in korean family by NGS - Ye-Ri Kim; Hye-Min Kim; Byeonghyeon Lee; Jeong-In Baek; Kyu-Yup Lee; Hong-Joon Park; Un-Kyung Kim (Genes & Genomics, 2023)

Exposure to China dust exacerbates testicular toxicity induced by cyclophosphamide in mice - Woong-Il Kim; Je-Oh Lim; So-Won Pak; Se-Jin Lee; In-Sik Shin; Changjong Moon; Jeong-Doo Heo; Jong-Choon Kim (Toxicological Research, 2023)

3-Hydroxymorphinan protects against hypoxia-induced cell death in primary astrocyte by regulating Ca2+ influx and the glutamate homeostasis - Ok-Hyeon Kim; Gyeong Yun Lee; Kyung Yong Kim; Jong In Son; Tae Woo Jung; Ji Hoon Jeong; Joon Seok Bang; Hyoung-Chun Kim; Yoon Hee Chung; Hyun Jung Lee (Molecular & Cellular Toxicology, 2023)

Description of Microbacterium neungamense sp. nov. isolated from a hot spring - Dariimaa Ganbat; Ga Eul Jeong; DoKyung Oh; Dong-Woo Lee; Yong-Jik Lee; Seong-Bo Kim; In-Tae Cha; Won-Jae Chi; Seul-Ki Park; Jung-Sook Lee; Sang-Jae Lee (Archives of Microbiology, 2023)

A Study on Slamming Impact Load Characteristics of Energy Storage System Case for Ships - In-Chul Park; Byoung-Cheon Seo; Sang-Hoon Lee; Jeong-Hoon Park; Hyoung-Seock Seo (Journal of Marine Science and Engineering, 2022)
As part of the environmentally friendly policy of ships, active research is being conducted on energy storage systems (ESS) for ships. This ESS has a major influence on determining the propulsion and operation system of the ship in the future. A separate space must be provided for the ESS, but small and medium-sized ships often require it to be located at the bottom of the ship to make use of the available space. If the ESS is located at the bottom of the ship, the slamming impact load should be considered, and a study of the vibrations generated during the slamming impact is required. Ships are subjected to various environmental effects while sailing. Among them, the risk factor caused by waves is one of the direct risk factors for the operation of the ship. This slamming phenomenon affects not only ships but also offshore structures, and is a risk factor that can cause structural damage as well as damage to human life. Therefore, it is necessary to study the slamming load, and a method is needed to address it with a dynamic load instead of a static load. In order to reflect the slamming load in the design as a dynamic load rather than the equivalent hydrostatic pressure, which is a static load, it is necessary to study the elastic effect of the structure. The plate thickness is calculated by considering the equivalent design pressure based on the measured slamming pressure peak, and several experimental and theoretical studies have been conducted to estimate the exact value of the peak pressure. However, according to recent studies, structural damage is affected not only by the peak pressure but also by the peak width in the time interval of the peak pressure. Research on slamming has been ongoing for a long time, but structural damage due to slamming is still being reported steadily. In order to understand the slamming phenomenon and reflect it in the structural design formula, high-quality experimental results are required. The slamming phenomenon occurs in a very short time. In order to obtain high-quality experimental results for this slamming phenomenon, numerous experimental variables such as experimental equipment setting, appropriate sensor selection, and data measurement and storage capability must be carefully considered. Normally the slamming load can be expressed in terms of peak pressure, peak width, and duration of the pressure, and the maximum pressure and the idealized pressure value (impulse) are applied to the structure. This slamming pressure is affected by the shape and natural period of the structure and shows the largest pressure value when the dead-rise angle is 3° to 10°. In this study, the test was performed by repeatedly dropping into the water using structural bottom angles of 0°, 3°, 10°, and 20° to the free surface of the water. The peak pressure, peak width, impulse, pressure coefficient, and traveling velocity of peak pressure obtained from the repeated tests are estimated with mean and coefficient of variation.

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Evaluation of genotoxicity of SUNACTIVE Zn-P240 in vitro and in vivo - Jeong-Hyun Lim; Jong-Yun Lee; Woong-Il Kim; So-Won Pak; Se-Jin Lee; In-Sik Shin; Jong-Choon Kim (Toxicological Research, 2022)

Subchronic Toxicity Evaluation of Aluminum Oxide Nanoparticles in Rats Following 28-Day Repeated Oral Administration - Sung-Hyeuk Park; Je-Oh Lim; Woong-Il Kim; So-Won Park; Se-Jin Lee; In-Sik Shin; Changjong Moon; Je-Hein Kim; Jeong-Doo Heo; Jong-Choon Kim (Biological Trace Element Research, 2022)

Persistent Continental Shelf Carbon Sink at the Ieodo Ocean Research Station in the Northern East China Sea - Kitack Lee; Ja-Myung Kim; Gyeong-Seok Lee; Eunil Lee; Jin-Yong Jeong; Jaeik Lee; In-Seong Han (Frontiers in Marine Science, 2022)
Hourly (2017–2021) to seasonal (2015–2021) inorganic C data were collected at the Ieodo Ocean Research Station (32.07°N and 125.10°E) in the northern East China Sea (ECS), located under the influence of the nutrient-rich Changjiang Diluted Water (CDW). An increase in phytoplankton biomass from April to mid-August (the warming period) equalized much of the temperature-driven increase in the surface pCO 2 and thus, made the northern ECS a moderate sink of atmospheric CO 2 . From November to March (the cooling period), a large pCO 2 reduction, driven by a temperature reduction, and a high air–sea CO 2 exchange rate, because of high windspeeds, transformed the basin into a substantial CO 2 sink, yielding an annual net C uptake of 61.7 g C m –2 yr –1 . The effects of biological production and temperature change on seawater pCO 2 (and thus, the net air–sea CO 2 flux) were decoupled each season and acted in concert to increase the net annual CO 2 sink by the region. The present study provided the observational and mechanistic lines of evidence for confirming “continental shelf C pump”—a mechanism in the shallow waters of the continental shelves that accumulate a significant amount of C ( via reinforced cooling and promoted biological C uptake) that is transported from the basin surface waters to the interior of the adjacent deep ocean. In the future, an increasing input of anthropogenic nutrients into the northern ECS is likely to make the region a stronger CO 2 sink.

A Comparative Study of an Anti-Thrombotic Small-Diameter Vascular Graft with Commercially Available e-PTFE Graft in a Porcine Carotid Model - Kyo Seon Lee; Mukhammad Kayumov; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Yun-Jin Jeong; Dong-Weon Lee; Jun-Kyu Park; Chan-Hee Park; Cheol-Sang Kim; Francis O. Obiweluozor; In-Seok Jeong (Tissue Engineering and Regenerative Medicine, 2022)
Background: We have designed a reinforced drug-loaded vascular graft composed of polycaprolactone (PCL) and polydioxanone (PDO) via a combination of electrospinning/3D printing approaches. To evaluate its potential for clinical application, we compared the in vivo blood compatibility and performance of PCL/PDO + 10%DY grafts doped with an antithrombotic drug (dipyridamole) with a commercial expanded polytetrafluoroethylene ( e -PTFE) graft in a porcine model. Methods: A total of 10 pigs (weight: 25–35 kg) were used in this study. We made a new 5-mm graft with PCL/PDO composite nanofiber via the electrospinning technique. We simultaneously implanted a commercially available e -PTFE graft ( n = 5) and our PCL/PDO + 10%DY graft ( n = 5) into the carotid arteries of the pigs. No anticoagulant/antiplatelet agent was administered during the follow-up period, and ultrasonography was performed weekly to confirm the patency of the two grafts in vivo . Four weeks later, we explanted and compared the performance of the two grafts by histological analysis and scanning electron microscopy (SEM). Results: No complications, such as sweating on the graft or significant bleeding from the needle hole site, were seen in the PCL/PDO + 10%DY graft immediately after implantation. Serial ultrasonographic examination and immunohistochemical analysis demonstrated that PCL/PDO + 10%DY grafts showed normal physiological blood flow and minimal lumen reduction, and pulsed synchronously with the native artery at 4 weeks after implantation. However, all e -PTFE grafts occluded within the study period. The luminal surface of the PCL/PDO + 10%DY graft in the transitional zone was fully covered with endothelial cells as observed by SEM. Conclusion: The PCL/PDO + 10%DY graft was well tolerated, and no adverse tissue reaction was observed in porcine carotid models during the short-term follow-up. Colonization of the graft by host endothelial and smooth muscle cells coupled with substantial extracellular matrix production marked the regenerative capability. Thus, this material may be an ideal substitute for vascular reconstruction and bypass surgeries. Long-term observations will be necessary to determine the anti-thrombotic and remodeling potential of this device.

Characterization of non-solvent- and thermal-induced phase separation applied polycaprolactone/demineralized bone matrix scaffold for bone tissue engineering - Soo in Kim; Na Eun Kim; Sunjae Park; Joo Hee Choi; Younghun Lee; Gayeong Jeon; Jeong Eun Song; Gilson Khang (In vitro models, 2022)

Sacubitril/valsartan reduces endoplasmic reticulum stress in a rat model of doxorubicin-induced cardiotoxicity - Byung Sik Kim; In-Hwa Park; A-Hyeon Lee; Hyun-Jin Kim; Young-Hyo Lim; Jeong-Hun Shin (Archives of Toxicology, 2022)

Land use types with different fertilization management affected isotope ratios of bulk and water-extractable C and N of soils in an intensive agricultural area - Young-Jae Jeong; Hyun-Jin Park; Byeong-Jun Jeon; Bo-Seong Seo; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2022)

Comparison of the pathogenicity of porcine reproductive and respiratory syndrome virus (PRRSV)-1 and PRRSV-2 in pregnant sows - Chang-Gi Jeong; Salik Nazki; Seung-Chai Kim; Amina Khatun; Yun-Hee Noh; Dong-Uk Lee; Sang Chul Kang; Byoung-Joo Seo; Myeon-Sik Yang; Sim-In Lee; In-Joong Yoon; Bumseok Kim; et al. (Archives of Virology, 2022)

Protective effect of berberine chloride against cisplatin-induced ototoxicity - Jong-Heun Kim; Jeong-In Baek; In-Kyu Lee; Un-Kyung Kim; Ye-Ri Kim; Kyu-Yup Lee (Genes & Genomics, 2022)
Background Cisplatin (CP) is an effective anticancer drug broadly used for various types of cancers, but it has shown ototoxicity that results from oxidative stress. Berberine has been reported for its anti-oxidative stress suggesting its therapeutic potential for many diseases such as colitis, diabetes, and vascular dementia. Objective Organ of Corti of postnatal day 3 mouse cochlear explants were used to compare hair cells after the treatment with cisplatin alone or with berberine chloride (BC) followed by CP. Methods We investigated the potential of the anti-oxidative effect of BC against the cisplatin-induced ototoxicity. We observed a reduced aberrant bundle of stereocilia in hair cells in CP with BC pre-treated group. Caspase-3 immunofluorescence and TUNEL assay supported the hypothesis that BC attenuates the apoptotic signals induced by CP. Reactive oxygen species level in the mitochondria were investigated by MitoSOX Red staining and the mitochondrial membrane potentials were compared by JC-1 assay. Results BC decreased ROS generation with preserved mitochondrial membrane potentials in mitochondria as well as reduced DNA fragmentation in hair cells. In summary, our data indicate that BC might act as antioxidant against CP by reducing the stress in mitochondria resulting in cell survival. Conclusion Our result suggests the therapeutic potential of BC for prevention of the detrimental effect of CP-induced ototoxicity.

Parasphingorhabdus halotolerans sp. nov. isolated from marine sediment in Jeju Island - So-Jeong Kim; Minji Kim; Ki-Eun Lee; In-Tae Cha; Soo-Je Park (Archives of Microbiology, 2021)

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

Rapid detection of plum pox virus by reverse transcription recombinase polymerase amplification - Hwi-Won Jeong; Hyo-Jeong Lee; In-Sook Cho; Ho-Jong Ju; Rae-Dong Jeong (Journal of Plant Diseases and Protection, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Metformin ameliorates animal models of dermatitis - Soo Young Choi; Chanmi Lee; Min-Jeong Heo; Yeong Min Choi; In-sook An; Seunghee Bae; Sungkwan An; Jin Hyuk Jung (Inflammopharmacology, 2020)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

4-MeO-PCP and 3-MeO-PCMo, new dissociative drugs, produce rewarding and reinforcing effects through activation of mesolimbic dopamine pathway and alteration of accumbal CREB, deltaFosB, and BDNF levels - Arvie Abiero; Chrislean Jun Botanas; Raly James Custodio; Leandro Val Sayson; Mikyung Kim; Hyun Jun Lee; Hee Jin Kim; Kun Won Lee; Youngdo Jeong; Joung-Wook Seo; In Soo Ryu; Yong Sup Lee; et al. (Psychopharmacology, 2020)

A sensitive UPLC–ESI–MS/MS method for the quantification of cinnamic acid in vivo and in vitro: application to pharmacokinetic and protein binding study in human plasma - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; In-Joon Oh; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2020)

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Hepatocyte CREBH deficiency aggravates inflammatory liver injury following chemokine-dependent neutrophil infiltration through upregulation of NF-κB p65 in mice - Jung-Ran Noh; Jae-Hoon Kim; Soon-Young Na; In Bok Lee; Yun Jeong Seo; Jung Hyeon Choi; Youngwon Seo; Tae Geol Lee; Hueng-Sik Choi; Yong-Hoon Kim; Chul-Ho Lee (Archives of Toxicology, 2020)

Genome-wide analysis of spatiotemporal gene expression patterns during floral organ development in Brassica rapa - Soo In Lee; Muthusamy Muthusamy; Muhammad Amjad Nawaz; Joon Ki Hong; Myung-Ho Lim; Jin A. Kim; Mi-Jeong Jeong (Molecular Genetics and Genomics, 2019)

Brassica rapa expansin-like B1 gene (BrEXLB1) regulate growth and development in transgenic Arabidopsis and elicits response to abiotic stresses - Panneerselvam Krishnamurthy; Muthusamy Muthusamy; Jin A. Kim; Mi-Jeong Jeong; Soo In Lee (Journal of Plant Biochemistry and Biotechnology, 2019)

A Yellow Sea Monitoring Platform and Its Scientific Applications - Yong Sun Kim; Chan Joo Jang; Jae Hoon Noh; Kyung-Tae Kim; Jae-Il Kwon; Yongchim Min; Jongmin Jeong; Jaeik Lee; In-Ki Min; Jae-Seol Shim; Do-Seong Byun; Jinkwon Kim; et al. (Frontiers in Marine Science, 2019)

Multidrug-resistant Acinetobacter baumannii infection in lung transplant recipients: risk factors and prognosis - Dong Hyun Oh; Yong Chan Kim; Eun Jin Kim; In Young Jung; Su Jin Jeong; Song Yee Kim; Moo Suk Park; Anes Kim; Jin Gu Lee; Hyo Chae Paik (Infectious Diseases, 2019)

Elevated carbon dioxide significantly improves ascorbic acid content, antioxidative properties and restricted biomass production in cruciferous vegetable seedlings - Muthusamy Muthusamy; Jung Eun Hwang; Suk Hee Kim; Jin A. Kim; Mi-Jeong Jeong; Hyeong Cheol Park; Soo In Lee (Plant Biotechnology Reports, 2019)

Tsunami hazard from submarine landslides: scenario-based assessment in the Ulleung Basin, East Sea (Japan Sea) - Roger Urgeles; Jang-Jun Bahk; Sang-Hoon Lee; Senay Horozal; Deniz Cukur; Seong-Pil Kim; Gil-Young Kim; Sueng-Won Jeong; In-Kwon Um (Geosciences Journal, 2019)

Correction to: Exocyst Complex Member EXOC5 Is Required for Survival of Hair Cells and Spiral Ganglion Neurons and Maintenance of Hearing - Byeonghyeon Lee; Jeong-In Baek; Hyehyun Min; Seung-Hyun Bae; Kyeonghye Moon; Min-A Kim; Ye-Ri Kim; Ben Fogelgren; Joshua H. Lipschutz; Kyu-Yup Lee; Jinwoong Bok; Un-Kyung Kim (Molecular Neurobiology, 2019)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)

Impact of soil moisture initialization on boreal summer subseasonal forecasts: mid-latitude surface air temperature and heat wave events - Eunkyo Seo; Myong-In Lee; Jee-Hoon Jeong; Randal D. Koster; Siegfried D. Schubert; Hye-Mi Kim; Daehyun Kim; Hyun-Suk Kang; Hyun-Kyung Kim; Craig MacLachlan; Adam A. Scaife (Climate Dynamics, 2019)

Re-evaluation of Morphological Diagnostic Characteristics of Hexapleomera Dudich, 1931 (Crustacea: Tanaidacea), with Description of a New Species - Jin Hee Wi; Chang-Keun Kang; In Tae Lee; Hyeon Gyeong Jeong (Ocean Science Journal, 2018)

Effects of CYP2C19 and CYP3A5 genetic polymorphisms on the pharmacokinetics of cilostazol and its active metabolites - Hye-In Lee; Ji-Young Byeon; Young-Hoon Kim; Choong-Min Lee; Chang-Ik Choi; Choon-Gon Jang; Jung-Woo Bae; Yun Jeong Lee; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2018)

Effects of three-dimensional spheroid culture on equine mesenchymal stem cell plasticity - Mi Jeong Park; Jienny Lee; Jeong Su Byeon; Da-Un Jeong; Na-Yeon Gu; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2018)

Recent Primary Production and Small Phytoplankton Contribution in the Yellow Sea during the Summer in 2016 - Hyo Keun Jang; Jae Jung Kang; Jae Hyung Lee; Myungjoon Kim; So Hyun Ahn; Jin-Yong Jeong; Mi Sun Yun; In-Seong Han; Sang Heon Lee (Ocean Science Journal, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Inverse agonist of ERRγ reduces cannabinoid receptor type 1-mediated induction of fibrinogen synthesis in mice with a high-fat diet-intoxicated liver - Yaochen Zhang; Don-Kyu Kim; Yoon Seok Jung; Yong-Hoon Kim; Yong Soo Lee; Jina Kim; Won-IL Jeong; In-Kyu Lee; Sung Jin Cho; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2018)

Exocyst Complex Member EXOC5 Is Required for Survival of Hair Cells and Spiral Ganglion Neurons and Maintenance of Hearing - Byeonghyeon Lee; Jeong-In Baek; Hyehyun Min; Seung-Hyun Bae; Kyeonghye Moon; Min-A Kim; Ye-Ri Kim; Ben Fogelgren; Joshua H. Lipschutz; Kyu-Yup Lee; Jinwoong Bok; Un-Kyung Kim (Molecular Neurobiology, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Genome-wide Characterization of Brassica rapa Genes Encoding Serine/arginine-rich Proteins: Expression and Alternative Splicing Events by Abiotic Stresses - Eun Kyung Yoon; Panneerselvam Krishnamurthy; Jin A. Kim; Mi-Jeong Jeong; Soo In Lee (Journal of Plant Biology, 2018)

Improved dissipation kinetic model to estimate permissible pre-harvest residue levels of pesticides in apples - Jeong-In Hwang; Hyo-Young Kim; Sang-Hyeob Lee; Se-Yeon Kwak; Andrew R. Zimmerman; Jang-Eok Kim (Environmental Monitoring and Assessment, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Genetic variability comparison of cultured Israeli carp (Cyprinus carpio) from Korea using microsatellites - Jung Eun Kim; In Bon Goo; Ju-ae Hwang; Hyeong Su Kim; Hye-Sung Choi; Jeong-Ho Lee (Genes & Genomics, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Intercomparison of Terrestrial Carbon Fluxes and Carbon Use Efficiency Simulated by CMIP5 Earth System Models - Dongmin Kim; Myong-In Lee; Su-Jong Jeong; Jungho Im; Dong Hyun Cha; Sanggyun Lee (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Fisetin protects H9c2 cardiomyoblast cells against H2O2-induced apoptosis through Akt and ERK1/2 signaling pathways - Jeong Soo Lee; Ji-Sook Lee; Kyung Jae Cha; Dae-Eun Kim; Daye Lee; Sun Young Jung; Eun-Seok Park; In Sik Kim (Molecular & Cellular Toxicology, 2018)

Effects of backcrossing on quality of strawberry fruit - Sun Yi Lee; Seung Yu Kim; Dae Young Kim; Ho Jeong Jeong; In Seok Um; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Sound waves increases the ascorbic acid content of alfalfa sprouts by affecting the expression of ascorbic acid biosynthesis-related genes - Joo Yeol Kim; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2017)

Plant growth promoting effect of Bacillus amyloliquefaciens H-2-5 on crop plants and influence on physiological changes in soybean under soil salinity - Min-Ji Kim; Ramalingam Radhakrishnan; Sang-Mo Kang; Young-Hyun You; Eun-Ju Jeong; Jong-Guk Kim; In-Jung Lee (Physiology and Molecular Biology of Plants, 2017)

Recovery of renal function after administration of adipose-tissue-derived stromal vascular fraction in rat model of acute kidney injury induced by ischemia/reperfusion injury - Chunwoo Lee; Myoung Jin Jang; Bo Hyun Kim; Jin Young Park; Dalsan You; In Gab Jeong; Jun Hyuk Hong; Choung-Soo Kim (Cell and Tissue Research, 2017)

Generation of α-1,3-galactosyltransferase knocked-out transgenic cloned pigs with knocked-in five human genes - Dae-Jin Kwon; Dong-Hwan Kim; In-Sul Hwang; Dong-Ern Kim; Hyung-Joo Kim; Jang-Seong Kim; Kichoon Lee; Gi-Sun Im; Jeong-Woong Lee; Seongsoo Hwang (Transgenic Research, 2017)

Overexpression of the OsbZIP66 transcription factor enhances drought tolerance of rice plants - Suin Yoon; Dong-Keun Lee; In Jeong Yu; Youn Shic Kim; Yang Do Choi; Ju-Kon Kim (Plant Biotechnology Reports, 2017)

Gene loss/retention and evolutionary pattern of ascorbic acid biosynthesis and recycling genes in Brassica rapa following whole genome triplication - Panneerselvam Krishnamurthy; Jin A. Kim; Mi-Jeong Jeong; Ill Sup Nou; Soo In Lee (Genes & Genomics, 2016)

Sound wave affects the expression of ethylene biosynthesis-related genes through control of transcription factors RIN and HB-1 - Joo Yeol Kim; Hye Ryun Ahn; Sun Tae Kim; Cheol Woo Min; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2016)

Genetic analysis of COL11A2 in Korean patients with autosomal dominant non-syndromic hearing loss - Sang-Joo Kim; Hong-Joon Park; Borum Sagong; Seung-Hyun Bae; Se-Kyung Oh; Jeong-In Baek; Jae Young Choi; Kyu-Yup Lee; Un-Kyung Kim (Genes & Genomics, 2016)

Reduction of GIGANTEA expression in transgenic Brassica rapa enhances salt tolerance - Jin A. Kim; Ha-eun Jung; Joon Ki Hong; Victor Hermand; C. Robertson McClung; Yeon-Hee Lee; Joo Yeol Kim; Soo In Lee; Mi-Jeong Jeong; Jungsun Kim; DaeJin Yun; WeoYeon Kim (Plant Cell Reports, 2016)

Mechanism of protection by diallyl disulfide against cyclophosphamide-induced spermatotoxicity and oxidative stress in rats - Sung-Hwan Kim; In-Chul Lee; Je-Won Ko; In-Sik Shin; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Local injection of granulocyte-colony stimulating factor accelerates wound healing in a rat excisional wound model - Guang-Yin Shen; In-Hwa Park; Yi-Sun Song; Hyun-Woo Joo; Yonggu Lee; Jeong-Hun Shin; Kyung-Soo Kim; Hyuck Kim (Tissue Engineering and Regenerative Medicine, 2016)

Protective effects of garlic oil against 1,3-dichloro-2-propanol-induced hepatotoxicity: role of CYP2E1 and MAPKs - Je-Won Ko; Sung-Hyeuk Park; In-Chul Lee; Sang-Min Lee; In-Sik Shin; Seong-Soo Kang; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Chondrogenic potential and anti-senescence effect of hypoxia on canine adipose mesenchymal stem cells - Jienny Lee; Jeong Su Byeon; Keum Sil Lee; Na-Yeon Gu; Gyeong Been Lee; Hee-Ryang Kim; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2016)

Transgenic Turfgrasses Expressing Hyperactive Ser599Ala Phytochrome A Mutant Exhibit Abiotic Stress Tolerance - Mayank Anand Gururani; Markkandan Ganesan; In-Ja Song; Yunjeong Han; Jeong-Il Kim; Hyo-Yeon Lee; Pill-Soon Song (Journal of Plant Growth Regulation, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Defining the RNA-binding glycine-rich (RBG) gene superfamily: new insights into nomenclature, phylogeny, and evolutionary trends obtained by genome-wide comparative analysis of Arabidopsis, Chinese cabbage, rice and maize genomes - Panneerselvam Krishnamurthy; Jin A Kim; Mi-Jeong Jeong; Chang Ho Kang; Soo In Lee (Molecular Genetics and Genomics, 2015)

Interpretation and estimation for dynamic mobility of chlorpyrifos in soils containing different organic matters - Jeong-In Hwang; Sung-Eun Lee; Jang-Eok Kim (Environmental Geochemistry and Health, 2015)

Mesenchymal signaling in dorsoventral differentiation of palatal epithelium - Wern-Joo Sohn; Gi-Jeong Gwon; Hyeng-Soo Kim; Sanjiv Neupane; Sung-Jin Cho; Jae-Hyung Lee; Hitoshi Yamamoto; Je-Yong Choi; Chang-Hyeon An; Youngkyun Lee; Hong-In Shin; Sanggyu Lee; et al. (Cell and Tissue Research, 2015)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Dopamine D4 receptors linked to protein kinase G are required for changes in dopamine release followed by locomotor activity after repeated cocaine administration - Jeong Hwan Oh; Dong Kun Lee; Yoon-Bo Shim; In Soo Ryu; Su Yeon Seo; Jieun Kim; Ju Hwan Yang; Hyun-Wook Cho; Eun Sang Choe (Experimental Brain Research, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Genome-wide analysis of the expansin gene superfamily reveals Brassica rapa-specific evolutionary dynamics upon whole genome triplication - Panneerselvam Krishnamurthy; Joon Ki Hong; Jin A Kim; Mi-Jeong Jeong; Yeon-Hee Lee; Soo In Lee (Molecular Genetics and Genomics, 2015)

Analysis of an ECG Record Database Reveals QT Interval Prolongation Potential of Famotidine in a Large Korean Population - Jaesuk Yun; Eun Hwangbo; Jongpill Lee; Chong-Run Chon; Peol A. Kim; In-Hye Jeong; Manyoung Park; Raewoong Park; Shin-Jung Kang; Donwoong Choi (Cardiovascular Toxicology, 2015)

Interdecadal change of interannual variability and predictability of two types of ENSO - Hye-In Jeong; Joong-Bae Ahn; June-Yi Lee; Andrea Alessandri; Harry H. Hendon (Climate Dynamics, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

ZnO nanoparticle induces apoptosis by ROS triggered mitochondrial pathway in human keratinocytes - Woo-In Ryu; Yoon-Hee Park; Hyun Cheol Bae; Jin Hee Kim; Sang Hoon Jeong; Hana Lee; Sang Wook Son (Molecular & Cellular Toxicology, 2014)

Phosphorylation of hypothalamic AMPK on serine485/491 related to sustained weight loss by alpha-lipoic acid in mice treated with olanzapine - Hyunjeong Kim; Minsun Park; Su-Kyoung Lee; Jihyeon Jeong; Kee Namkoong; Hyun-Sang Cho; Jin Young Park; Byung-In Lee; Eosu Kim (Psychopharmacology, 2014)

Regulation of jasmonic acid biosynthesis by silicon application during physical injury to Oryza sativa L. - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Waqas; Hee-Jeong Jeong; Duk-Hwan Kim; Jeong Sheop Shin; Jong-Guk Kim; Myung-Hun Yeon; In-Jung Lee (Journal of Plant Research, 2014)

Gene expression analysis reveals a functional role for the Ag-NPs-induced Egr-1 transcriptional factor in human keratinocytes - Gyeongmin Yoo; Sang Hoon Jeong; Woo In Ryu; Hana Lee; Jin Hee Kim; Hyun Cheol Bae; Sang Wook Son (Molecular & Cellular Toxicology, 2014)

Unveiling abundance and distribution of planktonic B acteria and A rchaea in a polynya in A mundsen S ea, A ntarctica - Jong‐Geol Kim; Soo‐Je Park; Zhe‐Xue Quan; Man‐Young Jung; In‐Tae Cha; So‐Jeong Kim; Kyoung‐Ho Kim; Eun‐Jin Yang; Young‐Nam Kim; Sang‐Hoon Lee; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary Polynyas, areas of open water surrounded by sea ice, are sites of intense primary production and ecological hotspots in the A ntarctic O cean. This study determined the spatial variation in communities of prokaryotes in a polynya in the A mundsen S ea using 454 pyrosequencing technology, and the results were compared with biotic and abiotic environmental factors. The bacterial abundance was correlated with that of phytoplankton, P haeocystis spp. and diatoms. A cluster analysis indicated that the bacterial communities in the surface waters of the polynya were distinct from those under the sea ice. Overall, two bacterial clades, P olaribacter (20–64%) and uncultivated O ceanospirillaceae (7–34%), dominated the surface water in the polynya while the P elagibacter clade was abundant at all depths (7–42%). The archaeal communities were not as diverse as the bacterial communities in the polynya, and marine group I was dominant (> 80%). Canonical correspondence analysis indicated that the oceanographic properties facilitated the development of distinct prokaryotic assemblages in the polynya. This analysis of the diversity and composition of the psychrophilic prokaryotes associated with high phytoplankton production provides new insights into the roles of prokaryotes in biogeochemical cycles in high‐latitude polynyas.

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Effects of strobe light stimulation on postnatal developing rat retina - Jung-a Shin; Eojin Jeong; In-Beom Kim; Hwa-young Lee (Experimental Brain Research, 2014)

Source Activation of P300 Correlates with Negative Symptom Severity in Patients with Schizophrenia - Do-Won Kim; Miseon Shim; Jeong-In Kim; Chang-Hwan Im; Seung-Hwan Lee (Brain Topography, 2014)

Catalytically active telomerase holoenzyme is assembled in the dense fibrillar component of the nucleolus during S phase - Ji Hoon Lee; Yang Sin Lee; Sun Ah Jeong; Prabhat Khadka; Jürgen Roth; In Kwon Chung (Histochemistry and Cell Biology, 2014)

Chloroform induces HIF-1α-dependent VEGF expression in human keratinocytes - Jae Jun Nam; Hana Lee; Hyun Cheol Bae; Jinhee Kim; Sang Hoon Jeong; Woo-In Ryu; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

Comparative genetic diversity of wild and hatchery-produced Pacific oyster (Crassostrea gigas) populations in Korea using multiplex PCR assays with nine polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Woo Jin Kim; Hyun Jeong Lim; Eun Mi Kim; Soon Gyu Byun; Young Baek Hur; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Genetic differences between wild and hatchery populations of red sea cucumber (Stichopus japonicus) inferred from microsatellite markers: implications for production and stocking programs design - Hye Suck An; Jang Wook Lee; Seong Wan Hong; Ha Neui Hong; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Desulfotomaculum tongense sp. nov., a moderately thermophilic sulfate-reducing bacterium isolated from a hydrothermal vent sediment collected from the Tofua Arc in the Tonga Trench - In-Tae Cha; Seong Woon Roh; So-Jeong Kim; Hee-Ji Hong; Hae-Won Lee; Wan-Taek Lim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Natronomonas gomsonensis sp. nov., isolated from a solar saltern - Tae-Yoon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Man-Young Jung; Sang-A Lee; Seong Woon Roh; Kyung June Yim; Takashi Itoh; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Perverted Head Impulse Test in Cerebellar Ataxia - Seong-Hae Jeong; Ji-Soo Kim; In Chul Baek; Jong Wook Shin; Hyunjin Jo; Ae Young Lee; Jae-Moon Kim (The Cerebellum, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

The relationship between antipsychotic D2 occupancy and change in frontal metabolism and working memory - Euitae Kim; Oliver D. Howes; Federico E. Turkheimer; Bo-Hyung Kim; Jae Min Jeong; Ji Who Kim; Jae Sung Lee; In-Jin Jang; Sang-Goo Shin; Shitij Kapur; Jun Soo Kwon (Psychopharmacology, 2013)

Effect of the size and surface charge of silica nanoparticles on cutaneous toxicity - Yoon-Hee Park; Hyun Cheol Bae; Yeonsue Jang; Sang Hoon Jeong; Ha Na Lee; Woo-In Ryu; Min Gun Yoo; Yu-Ri Kim; Meyoung-Kon Kim; Jong Kwon Lee; Jayoung Jeong; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

Influence of soil properties on the distribution of Deschampsia antarctica on King George Island, Maritime Antarctica - Jeong Soo Park; In-Young Ahn; Eun Ju Lee (Polar Biology, 2012)

A novel COCH mutation associated with autosomal dominant nonsyndromic hearing loss disrupts the structural stability of the vWFA2 domain - Hyun-Ju Cho; Hong-Joon Park; Maria Trexler; Hanka Venselaar; Kyu-Yup Lee; Nahid G. Robertson; Jeong-In Baek; Beom Sik Kang; Cynthia C. Morton; Gert Vriend; László Patthy; Un-Kyung Kim (Journal of Molecular Medicine, 2012)

Erratum to: Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekkhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

Sequence polymorphisms of Der f 1, Der p 1, Der f 2 and Der p 2 from Korean house dust mite isolates - Kyoung Yong Jeong; In-Yong Lee; Tai-Soon Yong; Jae-Hyun Lee; Eun-Jin Kim; Joo-Shil Lee; Chein-Soo Hong; Jung-Won Park (Experimental and Applied Acarology, 2012)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Genetic evolution of the H9N2 avian influenza virus in Korean poultry farms - Chang-Hee Lee; Sung-Hwan Byun; Youn-Jeong Lee; In-Pil Mo (Virus Genes, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Assessment of the APCC coupled MME suite in predicting the distinctive climate impacts of two flavors of ENSO during boreal winter - Hye-In Jeong; Doo Young Lee; Karumuri Ashok; Joong-Bae Ahn; June-Yi Lee; Jing-Jia Luo; Jae-Kyung E. Schemm; Harry H. Hendon; Karl Braganza; Yoo-Geun Ham (Climate Dynamics, 2012)

A molecular framework for risk assessment of a virus-tolerant transgenic pepper line - In Soon Pack; Yu-Jin Kim; Eun Soo Youk; Woo Kyu Lee; Won Kee Yoon; Kee Woong Park; Chang-Gi Kim; Chee Hark Harn; Hwan Mook Kim; Soon-Chun Jeong (Journal of Crop Science and Biotechnology, 2012)

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients - In-Wha Kim; Yoo Jin Moon; Eunhee Ji; Kyung Im Kim; Nayoung Han; Sung Ju Kim; Wan Gyoon Shin; Jongwon Ha; Jeong-Hyun Yoon; Hye Suk Lee; Jung Mi Oh (European Journal of Clinical Pharmacology, 2012)

Identification and characterization of stress resistance related genes of Brassica rapa - Nasar Uddin Ahmed; Jong-In Park; Hee-Jeong Jung; Mi-Suk Seo; Thamilarasan Senthil Kumar; In-Ho Lee; Ill-Sup Nou (Biotechnology Letters, 2012)

CYP2C9*3 and *13 alleles significantly affect the pharmacokinetics of irbesartan in healthy Korean subjects - Chang-Ik Choi; Mi-Jeong Kim; Eun-Kyung Chung; Hye-In Lee; Choon-Gon Jang; Jung-Woo Bae; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2012)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

QTL analysis of fruit length using rRAMP, WRKY, and AFLP markers in chili pepper - Heung-Ryul Lee; Ki-Taek Kim; Hyoun-Joung Kim; Jung-Heon Han; Jeong-Ho Kim; Seon-In Yeom; Hyun Jung Kim; Won-Hee Kang; Jinxia-Shi; Soung-Woo Park; Ik-Hyun Bae; Semin Lee; et al. (Horticulture, Environment, and Biotechnology, 2011)

Higher DNA repair activity is related with longer replicative life span in mammalian embryonic fibroblast cells - Seong-Hoon Park; Hong-Jun Kang; Hyun-Seok Kim; Min-Ju Kim; Jee-In Heo; Jeong-Hyeon Kim; Yoon-Jung Kho; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Biogerontology, 2011)

Temperature trends in the skin/surface, mid-troposphere and low stratosphere near Korea from satellite and ground measurements - Jung-Moon Yoo; Young-In Won; Young-Jun Cho; Myeong-Jae Jeong; Dong-Bin Shin; Suk-Jo Lee; Yu-Ri Lee; Soo-Min Oh; Soo-Jin Ban (Asia-Pacific Journal of Atmospheric Sciences, 2011)

The use of healthy volunteers instead of patients to inform drug dosing studies: a [11C]raclopride PET study - Euitae Kim; Oliver D. Howes; Bo-Hyung Kim; Kyung-Sang Yu; Jae Min Jeong; Jae Sung Lee; Su Jin Kim; In-Jin Jang; Jung Shin Park; Yong Gil Kim; Sang-Goo Shin; Federico E. Turkheimer; et al. (Psychopharmacology, 2011)

Expression and immunohistochemical localization of TMEM16A/anoctamin 1, a calcium-activated chloride channel in the mouse cochlea - Ji Hyun Jeon; Jae Woo Park; Jong Woo Lee; Sung Won Jeong; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2011)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Allometric equations and biomass expansion factors of Japanese red pine on the local level - Choonsig Kim; Jaeyeob Jeong; Rae-Hyun Kim; Yeong-Mo Son; Kyeong Hak Lee; Jin-Seoung Kim; In-Hyeop Park (Landscape and Ecological Engineering, 2011)

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

Anti-angiogenic effects of the water extract of HangAmDan (WEHAD), a Korean traditional medicine - Ji-Young Bang; Kyung-Soon Kim; Eung-Yoon Kim; Hwa-Seung Yoo; Yeon-Weol Lee; Chong-Kwan Cho; YoungJin Choi; Hyun-Ja Jeong; In-Cheol Kang (Science China Life Sciences, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Characterization of chemical properties of atmospheric aerosols over Anmyeon (South Korea), a super site under Global Atmosphere Watch - Sung-Hwa Park; A. S. Panicker; Dong-In Lee; Woon-Seon Jung; Sang-Min Jang; Min Jang; Dongchul Kim; Yu-Won Kim; Harrison Jeong (Journal of Atmospheric Chemistry, 2010)

Soft‐sediment deformation structures in Cretaceous non‐marine deposits of southeastern Gyeongsang Basin, Korea: Occurrences and origin - Hee‐Cheol Kang; In Sung Paik; Ho Il Lee; Jeong Eun Lee; Jong‐Hwa Chun (Island Arc, 2010)
A variety of soft‐sediment deformation structures formed during or shortly after deposition occurs in the Cretaceous Seongpori and Dadaepo Formations of the southeastern Gyeongsang Basin exposed along coastal areas of southeastern Korean Peninsula for 0.5–2 km. These are mostly present in a fluvial plain facies, with interbedded lacustrine deposits. In this study, the features of different kinds of soft‐sediment deformation structures have been interpreted on the basis of sedimentology of structure‐bearing deposits, comparison with normal sedimentary structures, timing and mechanism of deformation, and triggering mechanisms. The soft‐sediment deformation structures can be classified into four morphological groups: (i) load structures (load casts, ball‐and‐pillow structures); (ii) soft‐sediment intrusive structures (dish‐and‐pillars, clastic dykes, sills); (iii) ductile disturbed structures (convolute folds, slump structures); and (iv) brittle deformation structures (syndepositional faulting, dislocated breccia). The most probable triggering mechanisms resulting in these structures were seismic shocks. These interpretations are based on the following field observations: (i) location of the study area within tectonically active fault zone reactivated several times during the Cretaceous; (ii) deformation structures confined to single stratigraphic levels; (iii) lateral continuity and occurrences of various soft‐sediment deformation structures in the deformed level over large areas; (iv) absence of depositional slope to indicate gravity sliding or slumping; and (v) similarity to the structures produced experimentally. The soft‐sediment deformation structures in the study areas are thus interpreted to have been generated by seismic shocks with an estimated magnitude of M > 5, representing an intermittent record of the active tectonic and sedimentary processes during the development and evolution of two formations from the late Early Cretaceous to the Late Cretaceous.

Isolation and characterization of a Glutamate decarboxylase (GAD) gene and their differential expression in response to abiotic stresses from Panax ginseng C. A. Meyer - Jung-Hye Lee; Yu-Jin Kim; Dae-Young Jeong; Gayathri Sathiyaraj; Rama Krishna Pulla; Ju-Sun Shim; Jun-Gyo In; Deok-Chun Yang (Molecular Biology Reports, 2010)

Mutation in Wilted Dwarf and Lethal 1 (WDL1) causes abnormal cuticle formation and rapid water loss in rice - Jong-Jin Park; Ping Jin; Jinmi Yoon; Jung-Il Yang; Hee Joong Jeong; Kosala Ranathunge; Lukas Schreiber; Rochus Franke; In-Jung Lee; Gynheung An (Plant Molecular Biology, 2010)

Evaluation of the toxicological properties and hepatoprotective effects of PAI-N002, a mixture of herbal extracts, in rats - Sung-Hwan Kim; Jeong-Hyeon Lim; In-Sik Shin; Changjong Moon; Soo-Hyun Park; Sung-Ho Kim; Jung-Sik Lee; Eun-Hye Kwon; Jong-Choon Kim (Molecular & Cellular Toxicology, 2010)

Detection of replicating negative-sense RNAs in CaCo-2 cells infected with human astrovirus - So Young Jang; Weon Hwa Jeong; Mi Suk Kim; Young Min Lee; Jae In Lee; Gyu Cheol Lee; Soon Young Paik; Gwang Pyo Koh; Jong Min Kim; Chan Hee Lee (Archives of Virology, 2010)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

AtObgC, a plant ortholog of bacterial Obg, is a chloroplast-targeting GTPase essential for early embryogenesis - Woo Young Bang; Akira Hata; In Sil Jeong; Tetsuya Umeda; Takayuki Masuda; Ji Chen; Ishizaki Yoko; I Nengah Suwastika; Dae Won Kim; Chak Han Im; Byung Hyun Lee; Yuno Lee; et al. (Plant Molecular Biology, 2009)

Fatty acid composition in each structural part of soybean seed and sprout - Krishna Hari Dhakal; Yeon-Shin Jeong; Jeong-Dong Lee; In-Youl Baek; Tae-Joung Ha; Young-Hyun Hwang (Journal of Crop Science and Biotechnology, 2009)

Assessment of Gene Flow from Genetically Modified Anthracnose-Resistant Chili Pepper (Capsicum annuum L.) to a Conventional Crop - Chang-Gi Kim; Dae In Kim; Hyo-Jeong Kim; Ji Eun Park; Bumkyu Lee; Kee Woong Park; Soon-Chun Jeong; Kyung Hwa Choi; Joo Hee An; Kang-Hyun Cho; Young Soon Kim; Hwan Mook Kim (Journal of Plant Biology, 2009)

Inhibitory effect of immature plum on PMA-induced MMP-9 expression in human hepatocellular carcinoma - Mi Hee Yu; Hyo Gwon Im; Sung Gyu Lee; Dae-Ik Kim; Hwa Jeong Seo; In-Seon Lee (Natural Product Research, 2009)

Anti-Androgen Receptor Signaling and Prostate Cancer Inhibitory Effects of Sucrose- and Benzophenone-Compounds - Zhe Wang; Hyo-Jeong Lee; Lei Wang; Cheng Jiang; Nam-In Baek; Sung-Hoon Kim; Junxuan Lü (Pharmaceutical Research, 2009)

AGHR polymorphism and its associations with carcass traits in Harrwoo cattle - Sang-Hyun Han; In-Cheol Cho; Jin-Hyoung Kim; Moon-Suck Ko; Ha-Yeon Jeong; Hong-Shik Oh; Sung-Soo Lee (Genes & Genomics, 2009)

Antimicrobial effect and resistant regulation of Glycyrrhiza uralensis on methicillin-resistant Staphylococcus aureus - Ji-Won Lee; Young-Ju Ji; Mi-Hee Yu; Mi-Hyang Hwang Bo; Hwa-Jeong Seo; Sam-Pin Lee; In-Seon Lee (Natural Product Research, 2009)

Buprederm™, a New Transdermal Delivery System of Buprenorphine: Pharmacokinetic, Efficacy and Skin Irritancy Studies - In Park; Dongwon Kim; Jindeog Song; Chang Hoon In; Seung-Wei Jeong; Sang Hun Lee; Bumchan Min; Dongho Lee; Sun-Ok Kim (Pharmaceutical Research, 2008)

Involvement of p38 MAPK-mediated signaling in the calpeptin-mediated suppression of myogenic differentiation and fusion in C2C12 cells - Sung-Ho Kook; Ki-Choon Choi; Young-Ok Son; Kyung-Yeol Lee; In-Ho Hwang; Hyun-Jeong Lee; Wan-Tae Chung; Choon-Bong Lee; Jong-Sun Park; Jeong-Chae Lee (Molecular and Cellular Biochemistry, 2008)

Effects of ethanol extract from Saururus chinensis (Bour.) Baill on lipid and antioxidant metabolisms in rats fed a high-fat diet - Mi Hee Yu; Hyo Gwon Im; Ji-Won Lee; Mi-Hyang Hwang Bo; Hyun-Jeong Kim; Suk Kyung Kim; Shin Kyo Chung; In-Seon Lee (Natural Product Research, 2008)

Cyclic mechanical stress suppresses myogenic differentiation of adult bovine satellite cells through activation of extracellular signal-regulated kinase - Sung-Ho Kook; Young-Ok Son; Ki-Choon Choi; Hyun-Jeong Lee; Wan-Tae Chung; In-Ho Hwang; Jeong-Chae Lee (Molecular and Cellular Biochemistry, 2008)

Detection of gene flow from GM to non-GM watermelon in a field trial - Chang-Gi Kim; Bumkyu Lee; Dae In Kim; Ji Eun Park; Hyo-Jeong Kim; Kee Woong Park; Hoonbok Yi; Soon-Chun Jeong; Won Kee Yoon; Chee Hark Harn; Hwan Mook Kim (Journal of Plant Biology, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Mechanism by whichBacillus-Derived 2-Aminobenzoic acid inhibits the growth ofArabidopsis thaliana Roots - Lam Hoang; Kyung Sik Song; In Koo Rhee; Jeong Hoe Kim; Sangman Lee (Journal of Plant Biology, 2007)

Tissue expression and cellular localization of phospholipid hydroperoxide glutathione peroxidase (PHGPx) mRNA in male mice - In-Jeoung Baek; Dong-Suk Seo; Jung-Min Yon; Se-Ra Lee; Yan Jin; Sang Soep Nahm; Jae-Hwang Jeong; Young-Kug Choo; Jong-Koo Kang; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2007)

Determination of hypocentral parameters of local earthquakes using weighting factor based on take-off angle - In Kyeong Hahm; Woohan Kim; Jung Mo Lee; Jeong Soo Jeon (Geosciences Journal, 2007)

ENA Actimineral Resource A restores bone loss and bone quality in ovariectomized rats - Sun Hee Do; Sung-Yong Hwa; Won-Il Jeong; Ji-Won Lee; Hyun-Jung Kim; In-Seon Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Taxonomy of the Genus Sargassum (Fucales, Phaeophyceae) from Korea 2. subgenus Bactrophycus section Halochloa and Repentia - Jeong-Hyeon Ok; In-Gyu Lee (Algae, 2006)

An α3β4 subunit combination acts as a major functional nicotinic acetylcholine receptor in male rat pelvic ganglion neurons - Kyu-Sang Park; Seung-Kyu Cha; Min-Jeong Kim; Dae-Ran Kim; Seong-Woo Jeong; Joong-Woo Lee; In Deok Kong (Pflügers Archiv - European Journal of Physiology, 2006)

Monitoring the occurrence of genetically modified soybean and maize around cultivated fields and at a grain receiving port in Korea - Chang-Gi Kim; Hoonbok Yi; Sangkyu Park; Ji Eun Yeon; Do Young Kim; Dae In Kim; Kyu-Hwa Lee; Taek Chang Lee; In Soon Paek; Won Kee Yoon; Soon-Chun Jeong; Hwan Mook Kim (Journal of Plant Biology, 2006)

Biflavonoids inhibited phosphatase of regenerating liver-3 (PRL-3) - Sung-Kyu Choi; Hyun-Mi Oh; Su-Kyung Lee; Dae Gwin Jeong; Seong Eon Ryu; Kwang-Hee Son; Dong Cho Han; Nack-Do Sung; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Alcohol-induced bone degradation and its early detection in the alcohol-fed castrated rats - Sun Hee Do; Won Il Jeong; Da Hee Jeong; Mi-Ran Ki; In-Seon Lee; Dong-Mi Kwak; Tae Hwan Kim; Yoo Kyeong Kim; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2006)

Injectable Polysaccharide Microcapsules for Prolonged Release of Minocycline for the Treatment of Periodontitis - Yoon Jeong Park; Jue Yeon Lee; Hey Ri Yeom; Kyung Hwa Kim; Sang Chul Lee; In Kyoung Shim; Chong Pyoung Chung; Seung Jin Lee (Biotechnology Letters, 2005)

Fractal Stochastic Modeling of Spiking Activity in Suprachiasmatic Nucleus Neurons - Sung-IL Kim; Jaeseung Jeong; Yongho Kwak; Yang In Kim; Seung Hun Jung; Kyoung J. Lee (Journal of Computational Neuroscience, 2005)

Dynamical Heterogeneity of Suprachiasmatic Nucleus Neurons Based on Regularity and Determinism - Jaeseung Jeong; Yongho Kwak; Yang In Kim; Kyoung J. Lee (Journal of Computational Neuroscience, 2005)

Transforming Growth Factor (TGF)-β1 Releasing Tricalcium Phosphate/Chitosan Microgranules as Bone Substitutes - Jue-Yeon Lee; Yang-Jo Seol; Kyoung-Hwa Kim; Yong-Moo Lee; Yoon-Jeong Park; In-Chul Rhyu; Chong-Pyoung Chung; Seung-Jin Lee (Pharmaceutical Research, 2004)

Comparison and Analysis of the Complete Nucleotide Sequence of Foot-and-Mouth Disease Viruses from Animals in Korea and Other PanAsia Strains - Jae Ku Oem; Kwang Nyeong Lee; In Soo Cho; Soo Jeong Kye; Jong Hyeon Park; Yi Seok Joo (Virus Genes, 2004)

Chitosan sponges as tissue engineering scaffolds for bone formation - Yang-Jo Seol; Jue-Yeon Lee; Yoon-Jeong Park; Yong-Moo Lee; Young -Ku; In-Chul Rhyu; Seung-Jin Lee; Soo-Boo Han; Chong-Pyoung Chung (Biotechnology Letters, 2004)

Subcellular accumulation of Cu in the Antarctic bivalve Laternula elliptica from a naturally Cu-elevated bay of King George Island - Heeseon J. Choi; In-Young Ahn; Ko-Woon Kim; Yong-Suk Lee; In-Sook Lee; Kye-Heon Jeong (Polar Biology, 2003)

Stimulation of β-carotene synthesis by hydrogen peroxide in Blakeslea trispora - Jae-Cheol Jeong; In-Young Lee; Seon-Won Kim; Young-Hoon Park (Biotechnology Letters, 1999)

Characterization of PPO (polyphenol oxidase) cDNA in sweet persimmon (Diospyros kaki) - Sung Chul Bahn; Young Soo Chung; Jeong Sheop Shin; Chang Hoo Lee; Nam In Hyung (Journal of Plant Biology, 1999)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)

Korean analytical quality assurance (KAQUA) program for biological monitoring - J. S. Yang; Mi Young Lee; In Jeong Park; Young Hahn Moon; Seong-Kyu Kang (International Archives of Occupational and Environmental Health, 1997)